Revisiting the Feldstein-Horioka puzzle: an institutional sector view - Bebczuk, Ricardo Néstor (2010)
Working on a sample of OECD countries spanning the period 1970-2003, this paper contributes to the Feldstein-Horioka literature by making three main innovations: (1) It estimates, for the first time, regressions at the institutional sector level (households, corporations, and government); (2) It explores the asymmetry between current account deficits and surpluses; and (3) It uses advanced panel data techniques to deal with endogeneity and to distinguish long- and short-run effects. The conclusions of the paper are that: (i) The national Feldstein-Horioka coefficient is in the vicinity of 0.5, but sectoral coefficients are much lower, a puzzling result possibly explained by endogenous intersectoral saving and investment links; (iii) The FH coefficients are higher in deficit than in surplus years; and (iv) The long-run relationship is in all cases below 1, which raises the question as to whether the intertemporal budget constraint should be interpreted.